Pecuniary Inputs and their Applications to Intelligent Decision Making in Choice of Robotic and Conventional Surgeries in Gynecologic Oncology and Urology in A Private Sector Super Speciality Tertiary Care Hospital in Southern India. - Nair, Apoorva R.; Chougule, Sanjeev; Songa, Isaac Raj; Lakshmi R., Vani; Kamath, Sagarika; Kamath, Rajesh; Verma, Reena (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Introduction: Robotic surgery is highlighted as a new medical technology that has the ability to standardize surgical techniques and make minimally invasive surgery possible. It is particularly suitable for complex procedures that require a high level of precision. There is a lot of promise for future advancements in the field of robotic surgery. The market for surgical robots was estimated at USD 4.4 billion globally in 2022, and it is anticipated to rise at a CAGR of 18 % from 2023 to 2030. This study involves the departments of gynecologic oncology and urology and intends to analyze the costs of both procedures- robotic surgery and traditional open surgery, in order to determine which procedure is more cost-effective. Methods: This is a retrospective study carried out in a 1400 bedded private hospital in South India. A sample size of 249 was obtained from the departments of gynecologic oncology and urology. Medical records of the patients aged above 18 years who underwent robotic surgery and conventional open surgery were obtained and analysed. Results: Out of the 249 patients, 55 patients were from Gynecologic oncology and 194 patients were from Urology. The Independent sample T test showed that the total cost for robotic surgery was significantly more (p-value<0.001) than the same for non-robotic surgery. The cost of medicines in robotic surgery was significantly more (p-value <0.001) than the same for non-robotic surgery. The cost of consumables for robotic surgery was significantly more (p-value <0.001) than the same for non-robotic surgery. The length of stay for robotic surgery was significantly more (p-value = 0.008) than the same for non-robotic surgery. Discussion: The study shows that even if robotic surgery cost significantly more than conventional surgery, it is safer and the length of stay is lesser than for conventional surgery, which results in better bed utilization. Robotic surgery also has better clinical outcomes and lesser pain and complications.